2020
DOI: 10.3390/foods9101446
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of VOC and Sensory Characteristics of Stracciatella Cheese as Affected by Different Preservatives

Abstract: Undesired volatile organic compounds (VOCs) can negatively affect the flavor of fresh food products; especially those characterized by a mild and delicate aroma. Finding connections between chemical and sensory analyses is a useful way to better understand the arising of off-flavors. A study was conducted on stracciatella; a traditional Italian cream cheese that is emerging on international markets. Samples were prepared by adding two different preservatives (alone or combined): sorbic acid and an olive leaf e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…It can be considered that differences in the fatty acids composition of the ripened sausages could be linked to a different evolution of the oxidative phenomena occurring during ripening. Since PUFA double bonds as preferred substrates for oxidative reactions [11,15,46], our results suggested a lower oxidation of this lipid fraction in OLE samples than the control and other samples with OLE/NO, probably be due to the antioxidant activity of the OLE, as previously demonstrated [19][20][21]51].…”
Section: Fatty Acids Compositionsupporting
confidence: 78%
See 2 more Smart Citations
“…It can be considered that differences in the fatty acids composition of the ripened sausages could be linked to a different evolution of the oxidative phenomena occurring during ripening. Since PUFA double bonds as preferred substrates for oxidative reactions [11,15,46], our results suggested a lower oxidation of this lipid fraction in OLE samples than the control and other samples with OLE/NO, probably be due to the antioxidant activity of the OLE, as previously demonstrated [19][20][21]51].…”
Section: Fatty Acids Compositionsupporting
confidence: 78%
“…Ozaki et al [47] demonstrated that after 35 days of drying and after 60 days of storage, all dry sausages with beetroot and radish powder as natural nitrite could be consumed safely and no thermotolerant coliform bacteria were found in all treatments. Other works assayed the antimicrobial potential of OLE in different food products, such as olive preserves and fresh dairy products [21,50,51]. The inclusion of OLE in the olive-based pâté decreased the microbial number in treated samples and no pathogen growth was observed [50].…”
Section: Microbiological Analysis Nitrate and Nitrite Residualmentioning
confidence: 99%
See 1 more Smart Citation
“…However, consumers are increasingly reluctant to chemical additives, which makes it necessary to replace traditional preservatives with natural substances that have similar functions. Natrella et al [ 13 ] essayed the use of different preservatives to avoid the formation of undesirable volatile organic compounds (VOC) in stracciatella, a traditional Italian cream cheese. Samples of cheese were prepared by adding two different preservatives (sorbic acid and an olive leaf extract) alone or combined.…”
mentioning
confidence: 99%
“…They are added at a concentration of 0.4 to 0.5% of the mixture and act either by inducing a cationic salt bridge (a thermally induced cross‐linking between metal ions and plant protein), or a salting‐out effect (protein dehydration followed by heat denatured plant protein) or acting as an acid coagulant and, consequently, lowering the pH value to the isoelectric point of the protein. 121 , 123 , 136 (iii) Enzymes e.g., Sodom apple extract ( Calotropis procera ), Roselle calyces ( Hibiscus sabdariffa ), papain, microbial transglutaminase (100 U/100 mL of plant milk). 127 , 133 , 135 , 137 , 138 (iv) Cold, e.g.…”
Section: Formulation Of Plant‐based Cheese Alterna...mentioning
confidence: 99%